Supplied Food Consistency and Oral Functions of Institutionalized Elderly - Yoshiaki Nomura; Ikki Tsutsumi; Masatoshi Nagasaki; Hiromitsu Tsuda; Fumihiro Koga; Naho Kashima; Masahide Uraguchi; Ayako Okada; Erika Kakuta; Nobuhiro Hanada (Hindawi Limited, 2020)
Background. Maintaining good oral function is one of the goals of dental treatment. The Japanese national insurance system newly introduced the concept of management of oral function according to the life stage. For the application of management of oral functions of the elderly, seven kinds of examination is a must for the diagnosis: xerostomia, oral hygiene status, maximum occlusal pressure, tongue and labium function, tongue pressure, chewing ability, and swallowing function. We analyzed the relationship between oral functions and supplied food consistency. Methods. Oral functions and supplied food consistency of sixty-nine institutionalized elderly were investigated. There were 13 men and 56 women, and their mean age was 86.23 ± 7.02. Oral functions were measured and evaluated according to the Japanese insurance system. Data were analyzed by item response theory analysis, ROC analysis, and decision analysis. Results. By the item response theory analysis, tongue pressure and swallowing functions had high discrimination ability. The subjects who had malfunction of the tongue and labium all had processed food. The subjects with difficulty in swallowing, even without malfunction of the tongue and labium, all had processed food. Conclusion. Supplied food consistency may depend on the oral functions. However, as oral function has some dimension, a systematic evaluation system is necessary to decide the supplied food consistency.